A Semantic Analysis of Sentences, Utterances, and Presuppositions in Moana (2016) - Dian Frederica Tunliu; Haryo Adi Buwono; Mira Zaliyanti; Nova Dyah Pitaloka; Hilma Safitri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This article explores the roles and relationships between sentences, utterances, and presuppositions in creating meaning in the film Moana (2016). Using a qualitative semantic analysis approach,the study examines a selection of dialogues to reveal how these three linguistic elements interact with each other. The analysis indicates that the structural and functional differences between sentences (as grammatical forms), utterances (as actual contextual realizations), and presuppositions (as underlying meanings) are crucial for understanding the meaning intended by the speaker and interpreted by the listener. These findings underscore the importance of understanding these three concepts in the transition from semantics to pragmatics, particularly when analyzing meaning in audiovisual media, such as films.